Principles of Selection of the Content of Training Specialists in the Field of Computer Science to Create Applications Using the Capabilities of the Net Platform - Zoxidov Jahongir Botirxonovich (Genius Publishing Group, 2023)
Considering the principles of selecting the content of training of future specialists using the technologies of the .NET platform, we will focus on the concept of the content of education and the principles of selection that exist in Russian pedagogical science.
Keywords: principles; content; focus